Investigating the development of possible selves in teacher education: candidate perceptions of hopes, fears, and strategies - Gonzalez-Bravo, Jill Elaine (Kansas State University, 2015)
Today’s teachers must not only be content experts, they must be reflective practitioners competent in both theory and complex learning processes. They must prove capable of constructing classrooms to meet the diverse needs of each child within a culture of global competition and high stakes testing. Beginning teachers are more effective when they enter classrooms with a strong identity and sense of self as teacher. Unfortunately, there is limited understanding of teacher candidate identity development and limited research on effective preparation strategies to strengthen the complex process. A two-staged instrumental-intrinsic case study was developed to collect and analyze candidate possible self-strategies. The investigation gave voice to an often-neglected source of insight, teacher candidates. The theory of possible selves, as proposed by Marcus and Nurius (1986), served as a framework for interviews conducted with thirteen candidates from a private institution in the Midwest. The researcher utilized results from previous applications of the theory to teacher education and extended findings by employing the strategy development process (Ibarra, 1999), an aspect previously unapplied to teacher preparation. Research findings provided insight into participants’ past memories and present motivations. While passive observation appeared to play a minor role in participant strategies, there was a heavy reliance upon future collegial support. Participants also valued intentional effective clinical mentors and suggested structured opportunities to promote dialogue and feedback. Results aligned with previous research that identified modeling of effective instructional strategies as essential to teacher educator quality. However, an additional attribute emerged, affective modeling. Participants attributed affective traits and actions of teacher educators to personal perceptions of collegiality and student-centered instruction. Findings support the utilitarian, investigative, and evaluative qualities of the theory of possible selves. The applied theoretical framework allowed for the assessment of participants’ knowledge, skills, and dispositions, aided in the identification of perceived preparation needs, and served as an appraisal of preparation program effectiveness. The collection and analysis of candidates’ hopes, fears, and process strategies served to inform teacher educator practice and increased understanding in regards to external and internal influences that shape professional identity development.
Keywords: Candidate; Preservice; Identity; Possible selves; Teacher; Educational evaluation (0443); Education, General (0515); Teacher Education (0530)